Sitting from left on: Vera, Julij, Evgenija, Margarita. Standing from left on: Konkordija, Sergej, Fedor, Lidija
Sitting from left on: Vera, Julij, Evgenija, Margarita. Standing from left on: Konkordija, Sergej, Fedor, Lidija.